Semimetal transition in curved MoS2/ MoSe2 Van der Waals heterojunction by dispersion‑corrected density functional theory - Ramos Murillo, Manuel Antonio (2022)
We present a theoretical study for MoS2/MoSe2 Van der Waals heterojunction in the armchair direction, and periodicity in the y-direction, under the mechanical deformation process to explore electronic structure vs. curvature angle. Our findings reveal that the heterojunction maintains chemical stability, even under high deformation, and the bandgap of the heterojunction is inversely proportional to curvature angle; the shift from semiconductor—with a bandgap of 0.8 eV—to semimetal occurs at deformation angles as low as 5°, having a gapless material. The mentioned transition corresponds mainly to distortion of half-filled molybdenum d-orbitals and chalcogen–chalcogen p-orbitals overlapping near the Fermi level.